Free-Living Enterobacterium Pragia fontium 24613: Complete Genome Sequence and Metabolic Profiling. (23rd March 2017) - Snopková, Kateřina; Sedlář, Karel; Bosák, Juraj; Chaloupková, Eva; Sedláček, Ivo; Provazník, Ivo; Šmajs, David
Pragia fontium is one of the few species that belongs to the group of atypical hydrogen sulfide-producing enterobacteria. Unlike other members of this closely related group, P. fontium is not associated with any known host and has been reported as a free-living bacterium. Whole genome sequencing and metabolic fingerprinting confirmed the phylogenetic position of P. fontium inside the group of atypical H2 S producers. Genomic data have revealed that P. fontium 24613 has limited pathogenic potential, although there are signs of genome decay. Although the lack of specific virulence factors and no association with a host species suggest a free-living style, the signs of genome decay suggest a process of adaptation to an as-yet-unknown host.